A rare case of dicephalic parapagus conjoined twins diagnosed in the third trimester - Joseph Arkorful; Emmanuel Fredua Agyeman; Richmond Ashitey Nmai; Albert Dayor Piersson (Radiology Case Reports, 2025)
Dicephalic parapagus conjoined twins, a rarely occurring form of conjoined twinning has poor prognosis and remains a significant cause of perinatal deaths. Since majority of cases of conjoined twins are not compatible with life, early and reliable detection with diagnostic medical imaging remains crucial for adequate patient counselling, medical and surgical management. We present a case of dicephalic parapagus twin gestation with associated congenital anomalies detected for the first time with ultrasound in the third trimester in a 29-year-old pregnant woman. An initial first trimester ultrasound at 14 weeks gestational age was unremarkable.Ultrasound fetal anatomical survey in the third trimester remains reliable for the detection of rare fetal anomalies such as dicephalic parapagus twins that might have been missed in earlier scans. Continuous efforts should therefore be made for the inclusion of detailed anatomical survey in the early third trimester; particularly in women with unremarkable earlier ultrasound scans and in those reporting late for obstetric care.